Acute neuromuscular and cardiovascular effects of varying relative loads in cross-training modalities - Barba-Ruíz, Manuel; Hermosilla-Perona, Francisco; Fernández-Asensio, José Miguel; Da Silva-Grigoletto, Marzo Edir; Martín-Castellanos, Adrián; Heredia-Elvar, Juan Ramón (Frontiers in Physiology, 2025)
Training structures such as every minute on minute (EMOM), as many repetitions as possible (AMRAP), and rounds for time (RFT) have gained popularity for improving sport performance and general health. However, limited research exists on how different relative loads affect neuromuscular and cardiorespiratory responses. This study aimed to compare acute effects on heart rate (HR), mean propulsive velocity (MPV), velocity loss, and pacing in participants performing AMRAP, EMOM, and RFT using the same absolute but varying relative loads. Twenty-five participants with over a year of training experience in these structures performed squats, pull-ups, and shoulder press at varying relative intensities (<40%RM, 40–65%RM, and >65%RM). Results showed significant differences in MPV between modalities (p < 0.05), with RFT having higher MPV than AMRAP, especially at lower intensities (<40%RM). EMOM also had higher MPV than AMRAP, with minimal differences compared to RFT. Velocity loss patterns varied by intensity group, with AMRAP inducing higher intra- and inter-set losses than EMOM (p < 0.05). HR analysis revealed EMOM elicited the lowest HR values, followed by AMRAP and RFT, and a larger HR difference was noted in the lowest intensity group (p < 0.05). These findings suggest that prescribing relative loads, rather than absolute loads, is important for optimizing performance and managing fatigue in cross training.